7-O-Methylwogonin from Scutellaria baicalensis Disturbs Mitotic Progression by Inhibiting Plk1 Activity in Hep3B Cells - Woo, Sang-Uk; Jang, Hay-Ran; Chin, Young-Won; Yim, Hyungshin (Planta Medica, 2019)
Polo-like kinase 1, a mitotic Ser/Thr kinase, has emerged as a molecular target for the development of anticancer drugs. In this study, we found that polo-like kinase 1 activity was inhibited by 7-O-methylwogonin and related flavones, including baicalein, dihydrobaicalein, and viscidulin II, isolated from Scutellaria baicalensis. Although dihydrobaicalein exhibited the highest polo-like kinase 1 inhibitory activity among the four compounds, it also inhibited other kinases, such as vaccinia-related kinase 2 and polo-like kinase 2. Baicalein and viscidulin II also showed low selectivity to polo-like kinase 1 since they inhibited polo-like kinase 3 and polo-like kinase 2, respectively. However, 7-O-methylwogonin exhibited selective polo-like kinase 1 inhibitory activity, as evidenced from in vitro kinase assays based on fluorescence resonance energy transfer assays and ADP-Glo kinase assays. In addition, examination of mitotic morphology and immunostaining using specific antibodies for the mitotic markers, p-histone H3 and mitotic protein monoclonal 2, in Hep3B cells showed that 7-O-methylwogonin treatment increased mitotic cell populations due to inhibition of mitotic progression as a result of polo-like kinase 1 inhibition. The pattern of 7-O-methylwogonin-induced mitotic arrest was similar to that of BI 2536, a specific polo-like kinase 1 inhibitor. Thus, it was suggested that 7-O-methylwogonin disturbed mitotic progression by inhibiting polo-like kinase 1 activity. These data suggest that 7-O-methylwogonin, a polo-like kinase 1 inhibitor, may be a useful anticancer agent because of its polo-like kinase 1 selectivity and effectiveness.
Keywords: 7-O-methylwogonin; polo-like kinase 1; Scutellaria baicalensis; Lamiaceae; anticancer; mitosis